2011
DOI: 10.4103/0019-5154.84768
|View full text |Cite
|
Sign up to set email alerts
|

Utility of dermoscopy in alopecia areata

Abstract: Background:Alopecia areata (AA) shows several well-defined dermoscopic features which may help in confirming diagnosis in AA.Aims:We carried out a study to examine the dermoscopic features of AA and develop a protocol for diagnosis of AA by dermoscopy.Materials and Methods:Dermoscopy was performed in 66 patients with AA. Hanse HVS-500NP dermoscope (magnification of ×32 and ×140) was used.Results:The mean age of the patients (46 males and 20 females) was 26.85 years. The mean age of onset was 25.15 years. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 7 publications
16
59
1
Order By: Relevance
“…In our study, YDs were seen in 88% (44/50) of cases, similar to the other studies. [91011] However, some studies reported lesser incidence. [71213] This variation in results can be attributed to the difference in skin types (yellowish color of skin in Asians may make it difficult to perceive the YDs on dermoscopy), different shampooing habits, and difference in the type of dermoscope used.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, YDs were seen in 88% (44/50) of cases, similar to the other studies. [91011] However, some studies reported lesser incidence. [71213] This variation in results can be attributed to the difference in skin types (yellowish color of skin in Asians may make it difficult to perceive the YDs on dermoscopy), different shampooing habits, and difference in the type of dermoscope used.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, BD was seen in 58% of the cases, and the result was comparable to that of Karadag Köse and Güleç[11] and Mane et al . [10]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations